The Effect of Brainstorming Implementation on Students’ Engagement in Learning about Probability in Math Classes in Grade XI IPA at SMA ABC Cikarang - Elsar Agung Triansa; Juniriang Zendrato; Oce Datu Appulembang (Polyglot, 2016)
This research aims to determine the effects of brainstorming on students’ engagement in learning about probability. The method used in this research is the quasi-experimental with a non-equivalent control group. The sampling technique is in the form of a census. The data was collected through a questionnaire and analyzed by using non-parametric tests -- the Mann-Whitney U-test and the Wilcoxon Signed-Rank test with alpha level of 0.05. The results show that: 1) there was no significant difference on students’ engagement before and after the experiment in the group that was taught without brainstorming; 2) there was significant difference on students’ engagement before and after the experiment in the group taught with brainstorming; and 3) there was no significant difference on students’ engagement between the group that was taught with brainstorming and the group that was taught without brainstorming. The result of this research indicates that implementing brainstorming produces a positive effect on students’ engagement in learning about probability in math classes in grade XI IPA at SMA ABC Cikarang.BAHASA INDONESIA ABSTRAK: Penelitian ini bertujuan untuk menemukan pengaruh penerapan brainstorming terhadap keterlibatan siswa dalam mempelajari topik peluang.Metode yang digunakan dalam penelitian ini adalah quasi-eksperimen dengan desain non-equivalent control group. Data dikumpulkan melalui kuisioner dan dianalisis dengan uji non-parametrik, yaitu uji Mann-Whitney U dan uji Wilcoxon Signed-Rank dengan taraf signifikansi 0.05.Hasil penelitian menunjukkan bahwa: 1) tidak ada perbedaan yang signifikan dalam keterlibatan siswa antara sebelum dan sesudah perlakuan di grup yang diajar tanpa brainstorming (hasil uji Wilcoxon Signed-Rank: ); 2) ada perbedaan yang signifikan pada keterlibatan siswa antara sebelum dan sesudah perlakuan di grup yang diajar dengan brainstorming (hasil uji Wilcoxon Signed-Rank: ); dan 3) tidak ada perbedaan yang signifikan pada keterlibatan siswa antara grup yang diajar dengan brainstorming dan tanpa brainstorming (hasil uji Mann-Whitney U: ). Hasil dari penelitian ini mengindikasikan bahwa penerapan brainstorming memberikan pengaruh yang positif terhadap keterlibatan siswa dalam mempelajari peluang di pelajaran matematika kelas XI IPA SMA ABC Cikarang.